2022
DOI: 10.3390/ma15103653
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Physicochemical Properties of Stockpile and Ponded Coal Ash

Abstract: The article describes chemical and also selected physical properties of ponded high temperature fly ash (FA) and bottom ash (BA) from a Mělník lignite power plant located in the Czech Republic. The research was carried out on samples obtained from drills with a depth of up to 54 m and the age of the samples retrieved from the lowest layers of the stockpile dating back to 1960. At the same time, a comparison was made with fresh fly ash and fresh bottom ash obtained from the identical power plant. The study anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The XRD analysis coupled with Rietveld refinement was employed to qualitatively and quantitatively determine the mineral phases present within the obtained samples ( Figure 1 ; Table 1 ). The diffractograms reveal the formation of magnetite in the Fd-3m cubic crystal system as the single mineral phase within samples Fe 3 O 4 , Zn 0.1 Fe 2.9 O 4 , and Ce 0.1 Fe 2.9 O 4 , (according to JCPDS 01-084-2782 [ 33 , 34 ]). By contrast, the increase in the substitution degree to 16.66% leads to the occurrence of secondary mineral phases, namely ZnO and Ce 2 O 3 in the hexagonal crystal system (according to JCPDS 00-005-0664 [ 35 ] and JCPDS 00-023-1048 [ 36 ], respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The XRD analysis coupled with Rietveld refinement was employed to qualitatively and quantitatively determine the mineral phases present within the obtained samples ( Figure 1 ; Table 1 ). The diffractograms reveal the formation of magnetite in the Fd-3m cubic crystal system as the single mineral phase within samples Fe 3 O 4 , Zn 0.1 Fe 2.9 O 4 , and Ce 0.1 Fe 2.9 O 4 , (according to JCPDS 01-084-2782 [ 33 , 34 ]). By contrast, the increase in the substitution degree to 16.66% leads to the occurrence of secondary mineral phases, namely ZnO and Ce 2 O 3 in the hexagonal crystal system (according to JCPDS 00-005-0664 [ 35 ] and JCPDS 00-023-1048 [ 36 ], respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The XRD analysis was employed for assessing the mineralogical phases present within the samples, while the Rietveld refinement allowed for the determination of the unit cell parameters and the average crystallite size. As the diffractograms show ( Figure 1 ), magnetite in the Fd–3m cubic crystal system is the unique crystalline phase within all samples (according to JCPDS 01-084-2782 [ 17 , 18 ]). Therefore, it can be concluded that despite the high pressure and temperature conditions for the reaction, microwave-assisted hydrothermal synthesis does not lead to the formation of secondary phases.…”
Section: Resultsmentioning
confidence: 99%
“…Šulc et al [8] contributed an article entitled "A Study of Physicochemical Properties of Stockpile and Ponded Coal Ash". The article describes chemical and also selected physical properties of ponded high-temperature fly ash (FA) and bottom ash (BA) from a Mělník lignite power plant located in the Czech Republic.…”
Section: Contributionsmentioning
confidence: 99%